INVESTIGATION OF LIGHT INTENSITY OF LIGHT CURING UNITS AFTER DIFFERENT PERIODS OF USE - Georgi Georgiev; Tsanka Dikova; Vladimir Panov (Peytchinski Publishing, 2021)
Quartz-tungsten halogen light curing units (LCUs) have been the main source of light for the polymerization of resin based composites (RBCs) for several decades. Since the beginning of the 20th century, however, their use has been reduced due to the invention and improvement of LED LCUs. Various factors can cause a decrease in the light intensity of LED LCUs, one of which is diode aging. The aim of the present paper is to study the change in light intensity of LCUs after different periods of intensive use. For this purpose, the light intensity of 94 regularly used LED LCUs aged between 1 and 10 years was measured with a digital radiometer. The devices were used in conventional mode with maximum light intensity. It was found that regardless of the type and model of LCU, there is a direct relationship between the time of use and light intensity - the longer the operation period of a device is and the more used it is, the lower its intensity is. The decrease in light intensity as devices age is different for different models, as well as for different devices of the same model. In the studied LCUs with a 10-year period of use, 77.5% have light intensity lower than the required minimum of 400 mW/cm2, which makes them unusable. It can be concluded that dentists should regularly monitor and measure the light intensity of their LCUs, especially as they age, to ensure the longevity of their restorative procedures.